2021
DOI: 10.1016/j.heliyon.2021.e08208
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the monetary value of ecosystem services provided by Gaung – Batang Tuaka Peat Hydrological Unit (KHG), Riau Province

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The study yields compelling evidence of peatland contributions to local livelihoods reflecting in substantial economic value. The findings align with previous research in various provinces in Indonesia, especially provisioning and regulating services i.e., food, freshwater, raw materials, timber, and carbon sequestration [73,[78][79][80][81][82][83][84][85][86]. Provisioning services provide basic necessities for a good life; while regulating services check and balance the entire ecosystem from local up to global scales, constituting to good life, security, and health [34,87,88].…”
Section: Discussionsupporting
confidence: 85%
“…The study yields compelling evidence of peatland contributions to local livelihoods reflecting in substantial economic value. The findings align with previous research in various provinces in Indonesia, especially provisioning and regulating services i.e., food, freshwater, raw materials, timber, and carbon sequestration [73,[78][79][80][81][82][83][84][85][86]. Provisioning services provide basic necessities for a good life; while regulating services check and balance the entire ecosystem from local up to global scales, constituting to good life, security, and health [34,87,88].…”
Section: Discussionsupporting
confidence: 85%
“…The area of burned peatland was considerably lower in managed areas, but its socioeconomic impact was still significant. For instance, a previous study has found that the monetary value of ecosystem capacity-generating provisioning services declined after the massive peatland fire in 2015 (Rossita et al, 2021). In addition, the environmental impact of peatland fires has been addressed by many studies, highlighting reduced air quality and increased GHG emissions in a densely populated peatland area (Jayarathne et al, 2018;Marlier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there are variations in harvesting between each type of agroforestry product, which also causes variations in the timing of obtaining income from agroforestry products. Mixed garden cropping patterns provide varied income, namely routine, daily, weekly, monthly, seasonal, and yearly, so mixed planting provides sustainable results for farmers (Markum et al 2021;Rahmani et al 2021;Rossita et al 2021;Zega et al 2013). Based on components, the agroforestry pattern in Nanga Menterap Village can be classified into agrisilvicultural and agrosilvopastural.…”
Section: Agroforestry Patternmentioning
confidence: 99%